نماذج من العلوم الشّرعيّة وروّادها في حاضرة تلمسان خلال العهد الزّيّاني (Revue El-Wahat pour les Recherches et les Etudes, 2020)
The religious sciences in Tlemcen have witnessed a great prosperity, what led to the emergence of personalities who gave a share in the evolution of these sciences especially in the following fields: Study, teaching and writing. This has been proved through the spread of the mutation sciences in this era, especially the sciences of the Koran and exegesis (interpretation) and Science of Hadith (Prophetic Tradition) In addition to the jurisprudence science and its Principles Which had a positive impact on the authorship movement in the Zayani era, especially in Tlemcen, and in the Middle East in general. Tlemcen was a scientific metropolis and a shining center comparable to that of Fez and Meknes in Morocco, Kairouan and Tunisia in the lower Maghreb and even Cordoba, in its heyday, in Andalusia. Keywords-  Models Sharia sciences - Scholars - Koran sciences - Interpretation sciences - Hadith sciences - Jurisprudence and its origins - Tlemcen - Zayani era.